Indução de resistência a antracnose do feijoeiro por frações de filtrato de cultura e extrato de micélio de Trichoderma longibrachiatum - Dildey, Omari Dangelo Forlin (2017)
This study aimed to purify by chromatography elicitors from Trichoderma longibrachiatum culture filtrate and mycelium extract and to test them in phytoalexin phaseolin inducing and resistance induced to anthracnose in common bean. The sodium phosphate buffer at 0.05 M (SPB) was used as the control treatment and the ASM (Acibenzolar-S-Metil) was used as the standard induction treatment. Ion Exchange Chromatography (IEC) and Gel Filtration Chromatography (GFC) were performed to separate fractions with eliciting power from the culture filtrate (CF) and T. longibrachiatum mycelium extract (TME). For the purification of elicitors by IEC, from GFC, it were obtained one glycidic and five glycoproteins fractions, totaling six fractions. For purification from TME, it were obtained three protein, one glycidic and two glycoproteins fractions, totaling six fractions. In both, were obtained twelve fractions from IEC. These, in turn, were purified in GFC, being obtained a total of thirty seven fractions. Among these, there were fourteen fractions of TME were classified according to their nature, being three proteins, two glycogen and nine glycoproteins. There were twenty-three fractions from TME, wich were classified according to their nature, being four proteins, nine glycogen and ten glycoproteins. Of the fractions purified in CFG from FTC and TME, eight presented phaseolin inducer potential (F17, F23, F25, F27, F31, F38 and F46). The 10 treatments consisted of the eight fractions and two controls: ASM and control (TAP). Treatments were applied in one of the primary leaves (treated leaf (TL)), and the other primary leaf was not treated (untreated leaf (UL)) to verify the systemic effect. Three leaf samples were taken for determination of enzymatic activity: before applying the fractions, after application of the fractions and after the pathogen inoculation. The defense enzyme analysis was performed for Peroxidase (POX), Polyphenoloxidase (PFO), Catalase (CAT), Phenylalanine ammonia-lyase (PAL) and β-1,3-glucanase (β-GASE). At the end, it was performed an evaluation of severity in the primary leaf of common bean, on the fifth day after inoculation. The in vivo test data were subjected to analysis of variance. The purification of samples from FTC and EXM of T. longibrachiatum, from IEC and GFC indicated fractions with the presence of eliciting molecules. The fractions F17, F23 and F25 from FTC and F27, F29, F31, F38 and F46 from EXM were able to induce phaseolin synthesis in common bean hypocotyls. The POX, PFO and β-GASE Increased when applied in the TL after application of the fractions and after inoculation of the pathogen. The fractions did not alter CAT and FAL enzymatic activity. The fractions F17, F23 and F27 reduced the anthracnose severity in the local effect.